Nagari Pandam Gadang: Mutiara Tersembunyi di Kaki Gunung Omeh Kecamatan Gunuang Omeh, Kabupaten Lima Puluh Kota, Provinsi Sumatera Barat: (Kuliah Kerja Nyata Nagari Pandam Gadang, Universitas Negeri Padang) - Ika Parma Dewi; Siti Nur Fajriahni; Sulthan Trianda Arisco; Deha Mutrisa Ervita; Najla Afifah Aprilia; Cindi Cenora Taileleu; Jenia Tamara Larisa; Sultan Farhan Fadhlurrahman (Lembaga Pengembangan Kinerja Dosen, 2026)
Nagari Pandam Gadang is a village in Gunuang Omeh District, Lima Puluh Kota Regency, West Sumatra Province, with an area of 64.00 km² and a population of approximately 5,058. This article aims to present a comprehensive profile of the village, covering aspects of geography, history, public facilities, tourism potential, and the economic conditions of the community. The data in this article is compiled based on the Administrative Map created by KKN students from Padang State University in 2026, supported by field observations and related literature sources. Geographically, this village has a potential natural landscape for the development of the agricultural and tourism sectors. From a historical perspective, Nagari Pandam Gadang is known as the birthplace of national hero Ibrahim Datuk Tan Malaka. In addition, this village has natural tourism potential such as the Many Fish Tourism and the Lotus Cave, which have not been optimally managed. The community's economic condition is still dominated by the traditional agricultural sector. Therefore, an integrated development strategy is needed to improve community welfare through the sustainable utilization of local potential based on local wisdom.